Is inadequate play area in schools associated with overweight among students in Addis Ababa, Ethiopia? A comparative cross-sectional study - Moges, Tsedey; Gebremichael, Bereket; Shiferaw, Solomon; Yirgu, Robel (Epidemiology and health, 2018)
The prevalence of childhood obesity has more than doubled since it was formally recognized as a global epidemic in 1997. With the increasingly dwindling space for private schools in Ethiopia, unresolved concerns exist among the public regarding the possible effect of limited play areas in schools on overweight/obesity. This study intended to determine and compare the levels of overweight/obesity among adolescents in private schools with and without adequate play area in Addis Ababa, Ethiopia. A school-based comparative cross-sectional study was conducted among 1,276 adolescents. Twenty private schools were grouped into 2 groups based on the size of the play area. Data were collected using a pre-tested questionnaire and anthropometric measurements and analyzed using descriptive statistical tests and logistic regression. The magnitude of overweight/obesity was significantly higher in schools with inadequate play area (19.4%; 95% confidence interval [CI], 16.4 to 22.7) than in schools with adequate play area (14.6%; 95% CI, 11.9 to17.5). Inadequacy of the play area was also positively associated with overweight/obesity in the multiple logistic regression analysis (odds ratio [OR], 1.62; 95% CI, 1.05 to 2.51). Using private car transportation to and from school (OR, 2.27; 95% CI, 1.13 to 4.57), father's educational status (secondary school and above: OR, 2.54; 95% CI, 1.14 to 5.62), and middle wealth quintile (OR, 2.54; 95% CI, 1.50 to 4.33) were other factors significantly associated with overweight/obesity. Inadequate play area in schools was an important contributor to overweight/obesity. Sedentary behavior was also significantly associated with overweight/obesity.